Status of Tree Species Regeneration with Special Reference to the Role of Termite Mounds in a Moist Deciduous Sal Forest of Doon Valley - Chakraborty, Joyeeta Singh; Ram, Nirmal; Jeeva, V.; Singh, Sudhir (Indian Forester, 2017)
The present study attempts to assess regeneration of tree species in relation to the influence of termite mounds in a moist Sal forest of Doon valley. Vegetation survey was conducted in two zones, viz. mound-influenced zone and non-mound zone (as control). A total of twelve tree species were recorded in the forest with only five tree species constituting the overstorey. The three most frequent species viz. Shorea robusta, Syzigium cumini and Mallotus philippensis were common to both the zones with similar regeneration pattern, while rest of the two less frequent tree species regenerated differentially across mound and non-mound zones. Presence of termite mounds lowered species richness and selectively supported the dominant species in the tree layer nearly forming a pure Sal stand. Regeneration of Sal (Shorea robusta) was fair at the two zones with higher sapling density near the mounds. Overall, 27% tree species showed good to fair regeneration at the nonmound region while for the mound zone it was only 17%. Total density of the seedlings and adult tree species on the mounds was significantly lower (p<0.05) than non-mound area. Hence, in the present forest, termite mounds suppressed tree regeneration in general but partly favored Sal regeneration at certain growth stages.